The concept of smart tourism in the context of tourism information services. (February 2017) - Li, Yunpeng; Hu, Clark; Huang, Chao; Duan, Liqiong
Abstract: Smart tourism has become increasingly popular in mainland China. Different types of events and activities have been classified as smart tourism, leading to the misuse of the term. What, then, is smart tourism? How to define it? Although researchers have defined the term, there has not been any consensus on a widely accepted interpretation. The definition provided by this study emphasizes smart tourism as an individual tourist support system within the context of information services and an all-encompassing technology. This paper compares the characteristics of both traditional tourist information services and those incorporated in smart tourism. Based on the concepts, recommendations are provided and future research/industrial directions are discussed. For the Chinese tourism market, smart tourism represents a new direction implying a significant influence on tourist destinations, enterprises, and also tourists themselves. Highlights: Identifies changing concepts of smart tourism within the Chinese academic literature. Proposes the concept that smart tourism has at its core the tourist demand and ubiquitous technology. Utilizes the term 'informationization' to describe key aspects of smart tourism. Links smart tourism to big data analysis. Links smart tourism to Government e-commerce policies.